An assist for cognitive diagnostics in soccer (Part II): Development and validation of a task to measure working memory in a soccer-specific setting - Knöbel, Simon; Lautenbach, Franziska (Frontiers in Psychology, 2023)
Cognitive diagnostics is of increasing interest to researchers and practitioners in the context of talent identification and performance enhancement in professional soccer. Research addressing the relevance of cognitive skills has been based on the cognitive component approach (i.e., general cognitive processes) and the expert performance approach (i.e., sport-specific cognitive processes). Following the aim to combine the strengths of both approaches we have previously developed and validated tasks to measure inhibition and cognitive flexibility in a soccer-specific setting, including a soccer-specific motor response (Musculus, Lautenbach et al., 2022). In line with the general agreement on three core executive functions (Diamond, 2013), this further development of diagnosing executive functions is to be completed with a task for the assessment of working memory. For this purpose, 60 competitive amateur soccer players (Mage = 25.95, SDage = 4.59) first conducted a computer-based version of the n-back (3-back) task followed by a 3-back task that required a soccer-specific motor response (i.e., pass) performed in a soccer-specific setting (i.e., SoccerBot100). Results show good reliability for both tasks. With regard to convergent validity, significant correlations between the computerized and soccer-specific task could be determined in target trials for response time (r = .566) and accuracy (r = .363). Thus, the soccer-specific n-back task can be considered a valid instrument for assessing working memory and potentially allows soccer clubs to diagnose the three core executive functions in a consistent soccer-specific setting.